2011
DOI: 10.1007/978-3-642-21852-1_44
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Brain Dynamics of Team Coordination Part II: Neurobehavioral Performance

Abstract: In this study, pairs of subjects performed a team-intensive task with the shared goal of clearing a virtual room from threats. The neurobehavioral dynamics of both subjects was analyzed to identify signatures of efficient team work. An ecologically valid task of room clearing was designed and a novel analysis framework was developed to address the challenge of understanding complex, continuous social processes at both behavioral and brain levels. A companion paper detailed the design of the neurobehavioral tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…These results in terms of bands and areas of interest are coherent with previous knowledge both about the role of EEG alpha and beta bands [ 6 ], and about the central (sensory-motor system), and parietal (mirror neuron system) brain areas in human interaction and coordination [ 7 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results in terms of bands and areas of interest are coherent with previous knowledge both about the role of EEG alpha and beta bands [ 6 ], and about the central (sensory-motor system), and parietal (mirror neuron system) brain areas in human interaction and coordination [ 7 ].…”
Section: Discussionsupporting
confidence: 89%
“…The combination of behavioral data and brain signals (electroencephalogram (EEG)) were used to identify the presence of beta-gamma complex in coordinated activities [ 6 ] and a phy-complex neuromarker of social coordination [ 7 ]. In a task as well controlled as finger movement, Tognoli et al [ 7 ] found brain activity reduction in the occipital EEG alpha band and in EEG sensory motor rhythms during social interaction (while two subjects observed each other moving the finger), whereas coordination correlated with particular EEG rhythms, called phy, in the right centro-parietal brain area (increased phy indicates increased coordination).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the causal effect is significantly higher than chance level for both cooperation modalities in 7 out of 29 systems of variables explored (Table 2 ). The relevant Neurometrics are essentially related to activity of the frontal area in beta band as expected for their role in mentalizing processes and team coordination dynamics ( Tognoli et al , 2011 ; Chauvigné et al , 2018 ). On the one hand, these results fit well in SPC and hyperscanning frameworks, which have already demonstrated higher synchronized autonomic (Elkins et al , 2009b ; Ahonen et al , 2018 ) and cerebral activity ( Jahng et al , 2017 ; Yi et al , 2018 ) in case of cooperation.…”
Section: Discussionmentioning
confidence: 99%
“…Electro-ocular activities were also collected to identify blinks and saccades, and shielding and guarding ensured minimal contamination from noise-emitting equipment. For additional information, please refer to Tognoli et al ( 2011b ). The analyses described below were done on artifact corrected EEG.…”
Section: Methodsmentioning
confidence: 99%
“…Such is the notorious problem of people-matching that pervades many human activities. Although multiple behavioral studies of team coordination have been conducted (Fiore et al, 2003 ; Cooke et al, 2007 ; Woolley et al, 2007 ; Salas et al, 2008 ; Astolfi et al, 2010 ; Bourbousson et al, 2010 ; DeChurch and Mesmer-Magnus, 2010 ; Dodel et al, 2010 ; Gorman et al, 2010 ; Gorman and Cooke, 2011 ; Stevens et al, 2016 ; Nordham et al, 2018 ), the underlying neural processes are currently still largely unknown (Astolfi et al, 2010 ; Dodel et al, 2011 ; Stevens et al, 2011 ; Tognoli et al, 2011b ; Cooke et al, 2012 ; Likens et al, 2014 ). Team coordination implies that team members mutually adapt their behavior in anticipation of, and in response to, the behavior of their teammates.…”
Section: Introductionmentioning
confidence: 99%